P-92 CAN HONEY AND APICULTURAL DERIVATIVES HELP IN FATTY LIVER DISEASE? - Liena Martina Bravo Urquiza; Marcelo Andia Kohnenkampf; Raquel Bridi; Juan Esteban Oyarzun Isamitt (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: The increase in caloric intake has led to an obesity epidemic both in Chile and worldwide. This trend has contributed to a rise in the prevalence of metabolic diseases, such as insulin resistance, type 2 diabetes mellitus, and non-alcoholic fatty liver disease (NAFLD). NAFLD affects approximately 25% of the global population and can progress to severe stages such as non-alcoholic steatohepatitis (NASH), fibrosis, cirrhosis, and hepatocellular carcinoma. Currently, there is no formal protocol for the pharmacological treatment of NAFLD, making prevention and reversal crucial for improving quality of life and reducing public health costs. Honey and bee pollen, rich in antioxidants and known for their therapeutic properties, could offer a non-pharmaceutic alternative to manage this condition. Objective: This study aims to evaluate Chilean endemic honeys and bee pollens form Ulmo and Quillay, to determine their hepatoprotective effect in an in vitro cellular model. Patients / Materials and Methods: For the cell assays, the HUH7 cell line was used. The compound AAPH (2,2′-azobis(2-amidinopropane) dihydrochloride) was employed as a peroxyl radical generator to induce cellular damage. The hepatoprotective effect was evaluated by inducing cellular damage with AAPH (0.2 mM for 24 hours), followed by the addition of phenolic extracts from honeys or bee pollens at various concentrations. To isolate the effect of glucose, present in the honeys, artificial honey, created from a combination of different sugars, was used. Cell viability was determined using the Alamar Blue assay after 24 hours of incubation with the different treatments. Results and Discussion: Hepatoprotective results were obtained by evaluating cell viability in the presence of Ulmo honey, Quillay honey, and bee pollen. Treatment of cells with AAPH resulted in cellular damage, significantly decreasing cell viability. However, the addition of Ulmo honey, Quillay honey, and bee pollen in co-treatment with AAPH reversed this effect, significantly increasing cell viability. These findings indicate a hepatoprotective effect of Ulmo and Quillay honeys, as well as bee pollen on cell viability compromised by AAPH. The presence of bioactive compounds, such as antioxidants and flavonoids, in these apicultural derivatives may explain their ability to protect liver cells from AAPH-induced oxidative damage. Conclusions: In conclusion, Ulmo and Quillay honeys, as well as bee pollen, demonstrated to be effective hepatoprotective agents, suggesting their therapeutic potential in protecting liver health.